Curva de Kuznets ambiental para o Estado de Mato Grosso - Teixeira, Rudolph Fabiano Alves Pedroza [UNESP]; Bertella, Mario Augusto [UNESP]; Almeida, Luciana Togeira de [UNESP] (My University, 2012)
Issues concerning deforestation have become a crucial theme in the environmental world debate. In this picture, Mato Grosso State has become an unfavorable example because it represents 36% of the accumulated deforestation in the Brazilian Amazon. In order to investigate the relationship between deforestation and income growth, this paper estimates an Environmental Kuznets Curve (EKC) for 139 cities of Mato Grosso through spatial econometrics. Using data for the year 2006, we estimate an EKC for the deforestation per capita against income per capita and other variables controlling the spatial effects. The preliminary results indicate that an EKC exists in a reversed U shape, i. e., the income growth reduces environmental effects from the maximum point. However, introducing a cubic term for the income, the economic growth would not reveal any relationship with the deforestation in the Mato Grosso State.

As questões relativas ao desmatamento vêm ganhando destaque no debate ambiental mundial. Nesse cenário, o estado de Mato Grosso destaca-se de maneira negativa representando 36% do desmatamento acumulado na Amazônia brasileira. Com o objetivo de investigar a relação entre o desmatamento e o crescimento da renda, este trabalho estima uma Curva de Kuznets Ambiental (CKA) para 139 municípios de Mato Grosso. Usando dados para o ano de 2006, é estimada uma CKA para o desmatamento per capita contra a renda per capita, seu termo ao quadrado, a razão de bovinos pela área destinada à pecuária, a densidade demográfica, a extração de madeira per capita e os efeitos espaciais. Os resultados sugerem que existe uma CKA na forma de “U” invertido. No entanto, ao se incorporar um termo cúbico para a renda, o crescimento econômico deixaria de expressar qualquer relação com o desmatamento dos municípios mato-grossenses.
Environmental Kuznets Curve for the Mato Grosso state
Keywords: Environmental Kuznets Curve; Deforestation; Spatial econometrics; Curva de Kuznets ambiental; Desmatamento; Econometria ambiental